A Survey On Financial and Management Accounting Practices Among Small and Medium Enterprises in Malaysia - Isa, Che Ruhana; Saleh, Zakiah; Sapiei, Noor Sharoja (Asian Journal of Accounting Perspectives, 2008)
In the current business environment, firms are faced with intensifying competition locally and globally, and fast changes in customers and technologies. In this environment it is vital that small and medium enterprises (SMEs) are equipped with appropriate and modern financial and management accounting practices in order for them to survive and remain profitable. One of the factors that determine the performance of a business organization is effective use of financial and management accounting reports. However, thus far very little published evidence on accounting practices among SMEs in Malaysia is found. This study aims to examine the financial and management accounting practices among SMEs in Malaysia and to investigate perceived usefulness of accounting reports for decision making. A survey was carried out using the SMEs in manufacturing listed by SMIDEC, as the sampling frame. A total of 76 usable questionnaires were used for the final data analysis. The findings from the survey provide pertinent and useful insights into the current financial and management accounting practices and the level of perceived usefulness of the accounting reports among SMEs. The results of the study indicate that a majority of the firms surveyed prepare their financial and management accounting reports on a monthly basis. With regards to the purpose of financial accounting reports, the results show that preparing tax returns rank first, followed by providing information to shareholders, and providing information to government agencies. Management accounting reports provide the most useful information for planning and control, followed by product pricing and lastly, employee performance evaluation. Financial accounting reports were perceived to be more useful than management accounting reports. Among the financial accounting reports, profit and loss statement was considered as most useful, followed by cash flow and balance sheet. Among the management accounting reports, production report was rated highest in terms of usefulness, followed by budget and variance analysis.